Multiculturalism: Its Implementation in Islamic Education - Khabibah, Siti; Almas, Afiq Fikri; Irbathy, Shafa Alistiana; Kolis, Nur (MUADDIB Jurnal Kependidikan dan Keislaman, 2024)
The main purpose of multicultural education is to provide equal opportunities for male and female students to succeed in their education regardless of differences in race, ethnicity, ethnicity, religion, social class, and culture of origin as well as being applied in an educational model that opposes forms of racism and all forms of discrimination in schools and society by accepting and affirming the pluralism and diversity of students. This research tried to explore traditions, habitus, and ideology and the implementation of multiculturalism values articulated in the form of curriculum and teaching, vision, and social life in institutions. With field research data collected and tested for its validity in confirmability, transferability, dependability, and data triangulation, it was found that multicultural education was implemented by inserting multiculturalism values into the learning curriculum with the dimensions of content integration, knowledge construction, prejudice reduction, equitable pedagogy, and empowering school culture and social structure. Multicultural education is attached to the curriculum and learning strategies, including in every interaction between school members. This type of multicultural education in critical education is reflective. It becomes the basis for action for change in Indonesian society which develops democratic principles in real action in the school community. It reflects unity in diversity. This research is expected to contribute to describing a multicultural education model that strengthens the diversity of differences and accommodates them for improving the quality of Indonesian human education.